¿Cómo lee un lexicógrafo un diccionario? Intervenciones de Aníbal Echeverría y Reyes en un ejemplar del Diccionario de chilenismos (1875) de Zorobabel Rodríguez - Rojas, Darío; Cáceres, Valentina (El Colegio de México, 2026)
This piece of research analyses the almost four hundred handwritten interventions by the Chilean lexicographer Aníbal Echeverría y Reyes found in a copy of Zorobabel Rodríguez’s Diccionario de chilenismos (1875). It shows, firstly, that these interventions are part of specialised reading practices aimed at lexicographical production. In the case of Echeverría, they are part of the preparation of his own dictionary, Voces usadas en Chile (1900). As well as characterising these interventions and categorising them, we explain the relationship of this reading practice both with the figure of the individual reader (Echeverría y Reyes) and with the interpretative community (the Chilean Hispanist lexicographers of the late nineteenth century) of which he is a part and which gives meaning to his interventions.